Rhetoric, independence, and nationhood, 1760-1800 - Lucas, Stephen, 1946- (Rhetorical history of the United States, 2022)
"Few periods of American history have been studied more extensively or debated more intensely than the last four decades of the eighteenth century, during which the thirteen colonies declared their independence from Great Britain, won their independence on the battlefield, created the United States Constitution, and implemented a new national government. Scholars have approached these developments from a variety of perspectives--economic, social, political, religious, legal, and diplomatic, to name a few. This volume adopts a rhetorical perspective, which foregrounds the art of effective expression as a means of influencing political perceptions, values, and behaviors. It presents eleven essays by an interdisciplinary group of scholars who bring to bear a variety of methods, backgrounds, perspectives, and specializations. The essays illuminate key rhetors, works, controversies, and moments that helped shape American discourse and politics during the years 1760-1800."--